ChemInform Abstract: A Highly Efficient Copper and Ligand Free Protocol for the Room Temperature Sonogashira Reaction. Issue 21 (May 2015) - Gogoi, Ankur; Dewan, Anindita; Bora, Utpal
Abstract The protocol is equally efficient for cross coupling of aryl iodides with aryl acetylenes or aliphatic alkynes at room temperature.